(untitled) (Eurasian Research Bulletin, 2024)
The gastrointestinal (GI) condition of critically ill patients on prolonged mechanical ventilation (MV) is associated with a significantly elevated risk of serious complications. These complications include erosive and ulcerative lesions, gastrointestinal bleeding, pancreatitis, gastropathy, and ischemic damage to the mucosal lining. A variety of factors contribute to the onset of these conditions, including stress, ischemia, infections, and the side effects of medications used in treating the underlying illness. The prolonged use of MV further exacerbates these issues by disrupting normal tissue perfusion and compromising the protective barrier function of the mucosa. Additionally, the combination of systemic inflammation, immune suppression, and reduced gastric motility in these patients creates an environment where gastrointestinal complications are more likely to occur. Stress-induced hypersecretion of gastric acid and reduced blood flow to the gastric mucosa can lead to acute gastric injury, increasing the risk of bleeding and ulcer formation. Moreover, mechanical ventilation itself can alter the dynamics of the GI tract, contributing to issues such as gastric stasis, regurgitation, and even aspiration pneumonia